A Study On Career Progression For Women In Hotel Industry: Current Scenario (PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: The hospitality industry has no dearth of women joining the industry. In fact if we  have a look at the data available with various hotel management institutes, the success ratio of  girls to boys is very high. Still when it comes to the senior management positions in the hotels  like General Manager and other Head of Departments, it’s the men who rule the roost. Now  with the society being more accepting towards working women, the newer generation may see  different result. But with the current scenario still in existence, we should be expecting the same  results, hence giving us the need to explore the unbalanced dynamics of this mismatched career  progression between male and female employees. Objective: The purpose of the study was to  discover how successful women achieve their senior-level positions, how they balance their work  and family life, and what career advice they can offer to future hospitality leaders. Methodology: It involved interviews from female hotel employees through semi-structured questionnaire. The  interview was conducted on 35 female employees working at various positions in 8 different star  category hotels in the city Jaipur with an idea to explore the challenges faced by them in the  career ladder in hotel management. Results: A very fair distribution of job positions ranging  from associate to managers with 30 percent at associate level and 25percent at Managers leve  was seen. On an average, women did not feel that gender based discrimination is hindering their  chance to progress. Respondents felt lack of family support, nature of work career growth and  pay package as career barriers. Conclusion: The study may help students learn from successful  female hoteliers and perhaps increase their commitment to longevity in hotel careers. Also to  sensitize the male counterparts in the industry to the specific needs of the female employees in  phases of their professional life.
Keywords: Career of women; Hospitality Industry; Career Progression; Unbalanced dynamics